Exploring factors influencing EFL students’ lack of interests in English lessons - Noyan, Marselina; Usadiati, Wahyuningsih; Mafulah, Siti (Universitas Islam Malang, 2025)
Learning outcomes are significantly and positively influenced by students’ interest in learning. This means that students will learn more effectively if they are more interested and satisfied with what they are learning. Unfortunately, the issue of students' lack of interest in learning English has not been thoroughly studied yet. Therefore, the aim of this study is to find out the aspects that cause students' lack of interest in English lessons. A survey design was used with tenth grade students of a high school in Malang, Indonesia, as the subjects, using 14 sets of items in the questionnaire as the research instrument to obtain the data. The data were verified through interviews to confirm their consistency with the questionnaire result. The data were analyzed and displayed using percentages. The findings show that, on average, from the teacher’s side, the students’ lack of interest in English lessons were mostly due to the teacher’s materials and methods of teaching and personal relationship with the students. From the students’ side, most of their lack of interest is due to their own unreadiness to learn English. These findings suggest that teachers should improve their teaching methods, materials, and student engagement strategies to enhance students’ interest in learning English and achieve better learning outcomes.